Signaling legitimacy across institutional contexts—The intermediary role of corporate social responsibility rating agencies. (27th August 2019) - Kölbel, Julian F.; Busch, Timo
Abstract: Research Summary: Good corporate social responsibility (CSR) ratings can increase a firm's legitimacy and reduce its default risk. Yet, the interpretation of CSR varies between different countries. We investigate whether CSR ratings have a risk‐mitigating effect across different institutional contexts. We find that good CSR ratings have a general risk‐mitigating effect. Yet, we also find that the effect decreases when the rating agency is embedded in the institutional context of its home country and the rated firm operates in a country with a different culture or regulatory system. This suggests that a rating agency's country of origin and its embeddedness in that country's context play an important role in the relationship between CSR ratings and default risk. Managerial Summary: In this article, we investigate to what extent CSR rating agencies signal organizational legitimacy across institutional contexts. Specifically, we evaluate how institutional distance between the rating agency and the rated firm moderates the negative effect of the CSR rating on the firm's default risk. We compare two CSR rating agencies, OEKOM, which is strongly embedded in its institutional context, and ASSET4, which operates across diverse institutional contexts. Based on a panel of 604 firms in 13 countries from 2011 to 2016, we show that CSR ratings from both rating agencies have a risk‐mitigating main effect. Yet, only in the case of OEKOM is the effect negatively moderated by regulatory and cultural distance. Thus, the legitimating effect of institutionally embedded CSR rating agencies decreases with institutional distance.